2017
DOI: 10.1038/onc.2017.134
|View full text |Cite
|
Sign up to set email alerts
|

Tumour exosomes from cells harbouring PTPRZ1–MET fusion contribute to a malignant phenotype and temozolomide chemoresistance in glioblastoma

Abstract: Exosomes are carriers of pro-tumorigenic factors that participate in glioblastoma (GBM) progression, and many fusion genes are strong driver mutations in neoplasia and are involved in tumorigenesis. However, the ability of fusion genes to be transduced by exosomes is unknown. We characterized exosomes from GBM cells harbouring and not harbouring PTPRZ1–MET fusion (ZM fusion). We also determined the effect of the exosomes from ZM fusion cells (ZM exosomes) on pro-oncogenic secretions and showed that ZM exosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 49 publications
1
92
0
1
Order By: Relevance
“…Colon cancer cell exosomes highly enriched in Nterminal truncated isoforms of p73 mRNA were able to confer drug resistance on recipient cells [19]. Exosomes from glioblastoma cancer cells harboring a protein tyrosine phosphatase receptor type Z1MET fusion conferred temozolomide resistance on parental cells [20]. These ndings demonstrated that exosomes could transfer intercellular drug resistance from drugresistant to drugsensitive cancer cells.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Colon cancer cell exosomes highly enriched in Nterminal truncated isoforms of p73 mRNA were able to confer drug resistance on recipient cells [19]. Exosomes from glioblastoma cancer cells harboring a protein tyrosine phosphatase receptor type Z1MET fusion conferred temozolomide resistance on parental cells [20]. These ndings demonstrated that exosomes could transfer intercellular drug resistance from drugresistant to drugsensitive cancer cells.…”
Section: Discussionmentioning
confidence: 84%
“…Increasing evidence suggests that tumor cellderived exosomes provide critical signals in the development of chemoresistance [810]. Several studies have revealed that the delivery of key molecules by exosomes to tumor cells could lead to chemoresistance [19,20]. Among the main components in exosomal cargo, some molecules have been discovered acting as the vital regulating effect on chemoresistance [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our study provided an alternative therapeutic strategy for patients who have developed recurrent disease under TMZ-based standard therapy. Moreover, MET and ZM fusion are critical for chemoresistance in GBM (Huang et al, 2016;Zeng et al, 2017), and knock down of MET sensitizes tumor cell lines in response to TMZ treatment . Given the lack of therapeutic options for recurrent tumor under TMZ treatment, our study has provided a promising therapeutic strategy of PLB-1001 mono-and combinatorial treatments with TMZ chemotherapy for patients with MET alterations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the purpose for the exosome‐induced oncogenic transfer is largely undetermined, neither is the manner that this type of oncogenic transfer changes tumor growth and metastasis is occurring permanently or transiently. Although future explorations are needed, some researchers suggest it may relate to tumor chemoresistance, with recent evidence in glioblastoma demonstrated exosomes from cells harboring PTPRZ1‐MET fusion contribute to a malignant phenotype and temozolomide chemoresistance …”
Section: Exosomes In Sequential Processes Of Tumor Metastasismentioning
confidence: 99%